Spanish Version of a Scale to Evaluate the Quality of Work Life in Teachers: An Adaptation of Walton’s QWL Model in the Peruvian Context - Muguerza-Florián, Edgardo (2023)
Workers’ job satisfaction benefits the organization, which constitutes a competitive advantage. This is why the Quality of Work Life (QoWL) study has gained relevance in recent years. For this reason, various scales have been developed to evaluate this organizational variable constantly. However, to date, there is no evidence in the scientific literature of a Spanish version that evaluates the validity and reliability of these scales in a Peruvian context. Thus, this study aimed to translate into Spanish and adapt and analyze the validity and reliability of a scale to assess the quality of work life in Peruvian teachers based on Walton’s model. For this purpose, 457 regular basic education teachers from a private educational network located in the three regions of Peru were surveyed. The analyses used the Structural Equation Model (SEM) with the AMOS 24 statistical software. Confirmatory Factor Analysis provided an excellent fit model of eight factors and 31 elements (CMIN/DF = 2.351; CFI = 0.955; SRMR = 0.062; RMSEA = 0.054; Pclose = 0.052). It also demonstrated good internal consistency (α = between 0.806 and 0.938; CR = between 0.824 and 0.939; AVE = between 0.547 and 0.794). These results contribute to the study of QoWL in Peru.